Age, brain region, and gene dosage-differential transcriptomic changes in Shank3-mutant mice - Yoo, Taesun; Yoo, Ye-Eun; Kang, Hyojin; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2022)
Shank3 is an abundant excitatory postsynaptic scaffolding protein implicated in various neurodevelopmental disorders, including autism spectrum disorder (ASD), Phelan-McDermid syndrome, intellectual disability, and schizophrenia. Shank3-mutant mice show various molecular, synaptic, and behavioral deficits, but little is known about how transcriptomic phenotypes vary across different ages, brain regions, and gene dosages. Here, we report transcriptomic patterns in the forebrains of juvenile and adult homozygous Shank3-mutant mice that lack exons 14–16 and also the prefrontal, hippocampal, and striatal transcriptomes in adult heterozygous and homozygous Shank3-mutant mice. The juvenile and adult mutant transcriptomes show patterns opposite from and similar to those observed in ASD (termed reverse-ASD and ASD-like patterns), respectively. The juvenile transcriptomic changes accompany synaptic upregulations and ribosomal and mitochondrial downregulations, whereas the adult transcriptome show opposite changes. The prefrontal, hippocampal, and striatal transcriptomes show differential changes in ASD-related gene expressions and biological functions associated with synapse, ribosome, mitochondria, and spliceosome. These patterns also differ across heterozygous and homozygous Shank3-mutant mice. These results suggest age, brain region, and gene dosage-differential transcriptomic changes in Shank3-mutant mice.